Splenectomy Reports - Uluc Günay (Journal of Spleen And Liver Research, 2024)
Introduction It was seen that splenectomy creates a disability situation in an individual, and in order to eliminate it, people applied to health boards to get a report to eliminate their social and economic losses recognized to them. Objective To examine the reason for surgery, method of surgery and the type of report they wanted to receive in splenectomised patients who applied to the general surgery committee polyclinic in 2017-2018-2019-2020 and 2023 when the pandemic ended. Materials and Methods Patients who applied to general surgery outpatient clinics were asked whether they had any surgery related to general surgery, and epicrises and pathology results of splenectomised patients were seen and recorded. Results Of the 23 splenectomised patients, 15 were female and 8 were male. Of the 15 female patients, 3 were splenectomised for ovarian ca, 3 for gastric ca, 2 for distal pancreatic ca, 2 for lymphoma, 1 for colon ca, 1 for traumatic cause, 2 for ITP, 1 for sarcoidosis. In male patients, 4 were splenectomised for traumatic, 1 for colon ca, 1 for ITP, 1 for thalassemia major and 1 for CML. The mean age of female patients was 48.1 years and the mean age of male patients was 37.4 years. The most common reason for splenectomy in women was malignancy and the most common reason for splenectomy in men was trauma. Conclusion Splenectomized patients had applied to receive the most DSR.
Keywords: Splenectomy